PERANCANGAN ULANG UI/UX WEBSITE D’COFFEE CUP KE APLIKASI MOBILE DENGAN METODE DESIGN THINKING - Icha Sinaga; Seftin Fitri Ana Wati; Anindo Saka Fitri (Politeknik Bisnis Indonesia, 2024)
D'Coffee Cup in Surabaya has implemented a web-based application for food ordering, yet it faces a significant issue due to the absence of direct payment features, resulting in long queues at the cashier. Initial usability testing revealed a score of 42.5 out of 100. A study utilizing the User Experience Questionnaire (UEQ) indicated low scores in attractiveness (-1.46), perspicuity (-1.15), efficiency (-1.65), dependability (-1.33), stimulation (-1.48), and novelty (-1.42), highlighting deficiencies in both the usability and aesthetics of the application’s UI design. Following a redesign process using the Design Thinking methodology (Empathize, Define, Ideate, Prototype, Testing), usability testing demonstrated a significant improvement with a usability score of 88, indicating an excellent level of usability. Additionally, UEQ testing results showed benchmark values for all six aspects above average: attractiveness (2.24), perspicuity (1.98), efficiency (2.15), dependability (1.93), stimulation (2.18), and novelty (2.03). Post-redesign usability testing demonstrated a significant improvement with a usability score of 88, indicating an excellent level of usability. Additionally, UEQ testing results showed benchmark values for all six aspects above average: attractiveness (2.24), perspicuity (1.98), efficiency (2.15), dependability (1.93), stimulation (2.18), and novelty (2.03).